Proceedings International Conference on Indonesian Islam, Education and Science (ICONIS) 2017 - (Editor), Roko Patria Jati; (Editor), Faizal Risdianto (Institut Agama Islam Negeri IAIN Salatiga, 2017)
Religious discourse is one of the most important aspects to be examined in order to understand a social system where religious authorities play a very vital role. Religions have always shaped society in various ways; while at times there have been issues related to religious persecution, at other times religions have also lead to national and societal unity among people. Religious leaders, who are called as ulama in Islam, have the authority and the dominant power to articulate any religious discourse by means of texts, both in written and spoken formats for establishing a social system. There is a strong relationship between the ulama and the ummat which means the believers in an Islamic society. This relationship is often commented with other discourses such as politics, economics and other important ideas in a society. These discourses play a critical role in creating power dominance through creating an authoritarian system where the ulamas feel very convenient to give a verdict on the society regarding any political or social issues. It seems that the ulamas have unquestioned power regarding religion and they use it conveniently in order to superimpose their views even if they are partisan and parochial.Muhammadiyah and Nahdlatul UlamaÂ Â (Â NU) are the biggest Islamic social organization not only in Indonesia but also in the world. Both Islamic organisations have shifted the socio-religious discourses in Indonesia. Muhammadiyah which is earlier established, is well known as modernist Islamic organisation that is very keen to concern on philanthropy. While NU is traditionalistÂ Sunni IslamÂ group and it is as the biggest Islamic social organisation in Indonesia. This organisation was established on January 31, 1926 to preserve the local culture and maintain Aswaja (Ah-al-Sunnah wal Jamaâah) in Indonesia. Â Abdurrahman Wahid, the grandson of NU founder Hasyim Asyari, inherited the leadership from his father, and was later elected Presiden of the Republic of Indonesia in 1999. The NU is visible in the form of accepted traditional culture which is as part of Indonesian culture. Â The conggres of NU on 1-5 August 2015 declares itself as Islam Nusantara (Archipelagic Islam). This is an ijtihad, theological judgements based on the fundementals of religion, to elevate Islam as rahmat lil âalamiin (blessing for the entire universe). It is a concept of Islam which teaches its adherents to live together with others. Besides, this concept is also used to decrease social tensions between Islam and Â local cultures that have been existed before Islam entering to the society. For Muhammadiyah, Islam is not merely teaching peace but Islam should be progressive in the peaceful coexistence. Therefore Islam is not a religion as such, it is also civilisation.The issues are strongly relevant to current situation of Mulsims in the East and West, which have similar problem called humanity crisis such as Palestine in the East and Islamophobia in the West. However, Muslims still believe that Islamic value will be an alternative value for the future civilization both in the East and West. Besides, Islamic values have proved its history as ethical basis of civilizations. The shared values and cultures have been practised by people in the East and West for long time even when state nation (nationalism) had not been established yet. People to people contact around the world had been taken place to strengthen the shared culture (values). They have similar experience how Islam to manage the country which consists of diversity in culture and at the same time how to encounter social and communal problems such as radicalism, capitalism, and globalisation.